A New Report: Niger (Guizotia abyssinica), a new host of Phytoplasma in Madhya Pradesh India: A New Report: Niger (Guizotia abyssinica), a new host of Phytoplasma in Madhya Pradesh India - K N GUPTA; RAJNI BISEN; AKSHAY (Journal of Oilseeds Research, 2023)
Niger (Guizotia abyssinica) is one of the important minor oilseed crops in India. Phyllody disease on niger was noticed for the first time at Research Farm of Project Co-ordinating Unit, Sesame and Niger, JNKVV, Jabalpur (M.P.) during the year kharif 202021 and noticed again in 2021-22.